2020
DOI: 10.1016/j.mehy.2020.110231
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the renin-angiotensin system (RAS): A spark that sets the forest alight?

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has increased exponentially in numbers with more than 20 million people infected around the globe. It is clear that COVID-19 is not a simple viral pneumonia, but presents with unusual pathophysiological effects. Of special interest is that SARS-CoV-2 utilises the angiotensin-converting enzyme-2 (ACE2) for cell entry and therefore has a direct effect on the renin angiotensin system (RAS). The RAS is primarily responsible for blood pressure control via the classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 42 publications
0
88
0
10
Order By: Relevance
“…(Curran et al, 2020) provide a model of pathology in COVID-19 involving a number of systems including the RAAS system and suggest that COVID-19 disrupts regulatory networks. (Wiese et al, 2020) hypothesise that pathology in COVID-19 arises from an upregulation of the classical arm of the RAS pathway and a downregulation of the ‘protective arm’ of the RAS pathway. (Czick et al, 2020) suggest a role for RAS imbalance in multiple aspects of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…(Curran et al, 2020) provide a model of pathology in COVID-19 involving a number of systems including the RAAS system and suggest that COVID-19 disrupts regulatory networks. (Wiese et al, 2020) hypothesise that pathology in COVID-19 arises from an upregulation of the classical arm of the RAS pathway and a downregulation of the ‘protective arm’ of the RAS pathway. (Czick et al, 2020) suggest a role for RAS imbalance in multiple aspects of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…While the mechanisms of pathophysiology remain unclear, the critical role of the immune system in advancing the disease has been well documented [ 5 , 6 ]. Assessment of these immunopathological features has revealed two key events – 1.…”
Section: Pathogenesis and Complications Of Covid-19mentioning
confidence: 99%
“…Several clinical trials have reported safety of MSC administration in patients with severe ADRS with very few or no infusion related-adverse effects. Of key note is the prospective, double-blind multi-center, randomized trial (START study) wherein 10x10 6 BM-MSCs/kg body weight were transplanted intravenously into 40 ARDS patients. A significant decrease in Ang-2 levels was observed and attributed to reduced inflammation (61).…”
Section: Mesenchymal Stromal Cells (Mscs) To Target Hyperinflammation In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses angiotensin-converting enzyme-2 (ACE2) as a receptor for cell entry and, therefore, might have an effect on the renin–angiotensin system (RAS) in the body [1] , [2] . RAS imbalance has been implicated in the pathogenesis of hypertension, heart failure, and chronic kidney disorder, which are commonly treated with angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs).…”
mentioning
confidence: 99%